Moth eye‐inspired highly efficient, robust, and neutral‐colored semitransparent perovskite solar cells for building‐integrated photovoltaics. Issue 4 (15th June 2021) - Zhu, Yiyi; Shu, Lei; Zhang, Qianpeng; Zhu, Yudong; Poddar, Swapnadeep; Wang, Chen; He, Zhubing; Fan, Zhiyong
Abstract: Semi‐transparent perovskite solar cells (ST‐PSCs) engendered enormous attention for practical applications such as power generation windows. However, it is still challenging to achieve high‐performance, robust and neutral‐colored ST‐PSCs. Herein we demonstrate a moth‐eye‐inspired structure (MEIS) for light‐trapping photons in the wavelength range where the human eye is less perceptive. This biomimetic structure contributes to the improvements in ST‐PSCs performance and visual appearance simultaneously. Consequently, a record high figure‐of‐merit for ST‐PSC, defined as the product of power conversion efficiency and the average visible transmittance, is achieved. Meanwhile, the optical appearance is converted to a desired near‐neutral color after introducing the MEIS. The investigation of ST‐PSCs with long‐term stability is implemented via engineering blend ratio of halides. The modified device exhibited appealing tolerance against moisture and solar irradiation. This work reveals an in‐depth understanding of light trapping along with modifying the visual appearance of solar cells. Abstract : Herein, we demonstrate a moth‐eye‐inspired structure (MEIS) for light‐trapping photons in the wavelength range where the human eye is less perceptive. This biomimetic structure contributes to the improvements in semi‐transparent perovskite solar cell (PSCs) performance and visual appearance simultaneously. Consequently, a record high figure‐of‐merit for ST‐PSC, defined as the product of power conversion efficiency (PCE) and average visible transmittance (AVT), is achieved. Meanwhile, the optical appearance is converted to a desired near‐neutral color after introducing the MEIS.